Mandatory Operative Re-Exploration after Initial Debridement of Necrotizing Soft Tissue Infections: Is it Mandatory?. Issue 10 (October 2017) - Spence, Lara H.; Yan, Huan; Moazzez, Ashkan; Schwed, Alexander; Keeley, Jessica; Karimzada, Mohammad; Allison, Mari; Neville, Angela; Plurad, David; Putnam, Brant; De Virgilio, Christian; Kim, Dennis
Necrotizing soft tissue infections (NSTIs) are aggressive infections requiring prompt diagnosis and extensive surgical debridement. Traditionally, patients undergo mandatory re-exploration to ensure adequacy of source control. The purpose of this study is to determine if re-exploration in the operating room is mandatory for all patients with NSTIs. An eight-year retrospective analysis of adult patients with NSTIs was performed comparing two groups: mandatory operative re-exploration versus operative re-exploration based on clinical examination findings. Outcomes measured included mortality, number of debridements, and length of stay (LOS). Twenty-two per cent of patients underwent a mandatory re-exploration. These patients were older, had a higher incidence of diabetes, and a longer duration of symptoms. There were no significant differences between groups with regard to the physical examination, severity of sepsis, time to repeat debridements, or in-hospital mortality, whereas LOS and the total number of debridements were increased in mandatory re-exploration. Bacteremia and septic shock were predictive of the need for further debridement in patients in the operative re-exploration based on clinical examination findings group. Mandatory re-exploration after initial debridement may not be necessary in all patients with NSTIs. Instead, bedside wound checks may be a safe strategy to determine the need for further operative debridement.